Health Education on Stress Levels Facing Changes in Menstrual Patterns among Adolescents: Pendidikan Kesehatan tentang Tingkat Stress Menghadapi Perubahan Pola Menstruasi pada Remaja - Pande Putu Indah Purnamayanthi; Pande Putu Novi Ekajayanti; Ni Made Egar Adhiestiani (Poltekkes Kemenkes Palu, 2022)
Introduction: Current health education efforts through counseling are the right and acceptable way to increase young women's knowledge about stress so that it can affect menstrual patterns. Based on the data found, it shows that changes in abnormal menstrual patterns are related to psychological stress. The purpose of this service is to increase respondents' knowledge about how to manage stress when dealing with changes in menstrual patterns. Method: the method used in this service is counseling using Power Point media. which was held at SMA Denpasar with the number of respondents as many as 30 students. The evaluation used is by conducting questions and answers between the presenter and the respondent. Results: the results obtained are that after being given counseling the students better understand how to manage stress levels in dealing with menstrual patterns. From the results of the post test evaluation given, 26 students have understood the health education provided. It is hoped that by doing this counseling the students already have good knowledge and can be applied to everyday life.